Students’ Attitudes and Perceptions of Smart Online Learning through Podcast Content Development - Hernawan, Asep Herry; Dewi, Laksmi; Fadlillah, Ahmad Fajar; Setiawan, Budi (International journal of interactive mobile technologies, 2021)
Due to the COVID-19 pandemic spreading around the globe, it has affected many fields of human life, including educational services. It has been closed for months to eradicate the transmission of its virus. Corresponding to the situation, which changes dramatically, the educational institutions made some transformations and innovations to keep the class and instructional running safely for all by moving the regular sitting class face-to-face to online learning. Educational institutions, as well as podcasts, have developed several online learning media. This study explored the students' attitudes and preference towards creating content for online learning materials/ content by utilizing podcasts in innovative learning through an online survey of 84 students. The study results showed that most respondents (80%) stated that they were about to be enthusiastic, welcoming a new pattern of the instructional process by applying podcasts to develop subject content. The ﬁndings show the respondents’ attitudes and perceptions toward Podcast Content Development for Smart Learning are very positive with efficiency (80%), accessibility (90%), interactivity (90%), quality (82%).  They preferred to access online learning materials by maximizing the smartphone as its effective and efficient reason. They tend to have brief and meaningful content considering the size and broadband connectivity to achieve flexible and convenient online classes for smart learning